Epidemiological and Microbiological Aspects of the Peritonsillar Abscess - Slouka, David; Hanakova, Jana; Kostlivy, Tomas; Skopek, Petr; Kubec, Vojtech; Babuska, Vaclav; Pecen, Ladislav; Topolcan, Ondřej; Kucera, Radek (International journal of environmental research and public health, 2020)
Peritonsillar abscess (PTA) is the most common complication of tonsillitis. Cultivation usually reveals a wide spectrum of aerobic and anaerobic microbiota. This retrospective study compared PTA incidence and the spectrum of individual microbial findings in groups of patients divided by gender, age, and season. Of the 966 samples cultivated, a positive cultivation finding was detected in 606 patients (62.73%). Cultivation findings were negative in 360 (37.27%), meaning no pathogen was present or only common microbiota was cultivated. The highest incidence of PTA was found in group I patients (19-50 years) (p ≤ 0.0001) and the most frequently cultured pathogens was Streptococcus pyogenes (36.23%). Gender seemed to have an influence on the results, with higher incidence found in males (p ≤ 0.0001). The analysis of correlation between PTA incidence and season did not yield statistically significant results (p = 0.4396) and no statistically significant differences were observed in individual pathogen frequency. PTA had a higher incidence in adult males and a slightly higher incidence in girls in childhood. The following findings are clinically significant and have implications for antibiotic treatment strategy: (1) the most frequently cultivated pathogen was Streptococcus pyogenes; (2) an increased incidence of anaerobes was proven in the oldest group (>50 years).
Keywords: dospělí; peritonzilární absces; Female; dítě; Adult; ženské pohlaví; lidé; Anti-Bacterial Agents; Peritonsillar Abscess; Streptococcus pyogenes; Incidence; retrospektivní studie; Male; incidence; Child; mužské pohlaví; antibakteriální látky; Retrospective Studies; Humans